2019
DOI: 10.3991/ijep.v9i3.9876
|View full text |Cite
|
Sign up to set email alerts
|

Gruendungsgarage – A Best-Practice Example of an Academic Start-up Accelerator

Abstract: Over the past four decades, entrepreneurship has grown within universities faster than virtually any other area of intellectual pursuit. And it appears that the pace is accelerating with more universities seeking to develop programs and centers fo-cused on entrepreneurship. Yet, understanding how to build entrepreneurship programs that empower and transform has remained challenging for some institu-tions. This paper investigated the development of an entrepreneurship program called Gruendungsgarage [1]. The Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The extended intervention (n=36) involves the inclusion of additional services to typical interventions based on the participants' needs. The most commonly offered additional services include: office space (Clarysse et al 2015;Clarysse and Yusubova 2014;Connolly et al 2018;Drori and Wright 2018;Fernandes 2016;Gonzalez-Uribe and Leatherbee 2016;Goswami et al 2018;Grilo et al 2017;Gutstein and Brem 2018;Kanbach and Stubner 2016;Lall et al 2013;Miles et al 2017;Radojevich-Kelley and Hoffman 2012;Thompson 2012;Uhm et al 2018;Vandeweghe and Fu 2018); free housing (Bliemel et al 2019;Brown et al 2019;Fernandes 2016;Fraiberg 2017;Harima and Freudenberg 2019;Thompson 2012;Uhm et al 2018); and building a product (Caley and Kula 2013;Glinik 2019;Grilo et al 2017;Malek et al 2014;Shao and Shi 2018;Vandeweghe and Fu 2018). Less observed are services such as: financial and legal support (Clarysse et al 2015;Gardner and Webster 2017;Glinik 2019;Grilo et al 2017;Shao and Shi 2018;Thompson 2012); stipends (Connolly et al 2018;Thompson 2012); catering, materials needed for the workshop, and participant incentives are arranged (Gutstein and Brem 2018);...…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extended intervention (n=36) involves the inclusion of additional services to typical interventions based on the participants' needs. The most commonly offered additional services include: office space (Clarysse et al 2015;Clarysse and Yusubova 2014;Connolly et al 2018;Drori and Wright 2018;Fernandes 2016;Gonzalez-Uribe and Leatherbee 2016;Goswami et al 2018;Grilo et al 2017;Gutstein and Brem 2018;Kanbach and Stubner 2016;Lall et al 2013;Miles et al 2017;Radojevich-Kelley and Hoffman 2012;Thompson 2012;Uhm et al 2018;Vandeweghe and Fu 2018); free housing (Bliemel et al 2019;Brown et al 2019;Fernandes 2016;Fraiberg 2017;Harima and Freudenberg 2019;Thompson 2012;Uhm et al 2018); and building a product (Caley and Kula 2013;Glinik 2019;Grilo et al 2017;Malek et al 2014;Shao and Shi 2018;Vandeweghe and Fu 2018). Less observed are services such as: financial and legal support (Clarysse et al 2015;Gardner and Webster 2017;Glinik 2019;Grilo et al 2017;Shao and Shi 2018;Thompson 2012); stipends (Connolly et al 2018;Thompson 2012); catering, materials needed for the workshop, and participant incentives are arranged (Gutstein and Brem 2018);...…”
Section: Interventionsmentioning
confidence: 99%
“…Our review of interventions revealed a proliferation of extended approaches to deliver services to startup firms, going beyond the typical bundle of services to include a range of additional new services such as lean startup training (Mansoori 2017;Uhm et al 2018), and design thinking (Glinik 2019) often delivered in innovative ways, such as through the use of open innovation (Gutstein and Brem 2018) and living lab approaches (Haukipuro et al 2019). Changes in the way in which these services are provided, either through a standard package or through customization (Breznitz and Zhang 2019), has also been observed.…”
Section: How To Understand What Accelerators Do: Shortcomings and Future Researchmentioning
confidence: 99%
“…One of the materials covered in workshop for starter is mindset shifting to Entrepreneurship. Making use of alumni as partner to give workshop is said to be the stronger integration between alumni and the current students as beginners in the knowledge transfer and the exchange of experience (Glinik, 2019). There are other five topics of the workshop for starter level.…”
Section: How To Empower Entrepreneurship For Students Of Collegementioning
confidence: 99%
“…They just try to start a business and think that it will run smoothly and do not have a long term plan for the business. A study revealed that relevant skills and mindset acquired for entrepreneurship can be prepared by giving appropriate education at university levels (Glinik, 2019). In addition to mindset, motivation is also a necessary factor in starting and running a business for it influences the business in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few examples targeting the entrepreneurial intention is the course "Gruendungsgarage" (GG, "Founders´ garage"), offered at Graz University of Technology (TUG) [14]. The GG course aims to offer an authentic entrepreneurship experience, as it guides start-ups from their first idea to a professional business that can stand on its own feet.…”
Section: 1mentioning
confidence: 99%